Bionic design and performance test of maize grain cleaning screen through earthworm motion characteristics - Wang, Lijun; Yu, Yongtao; Zhang, Shuai; Feng, Xin; Song, Lianglai (International Journal of Agricultural and Biological Engineering, 2021)
The maize mixture feeding with a large mass cannot be migrated backward rapidly along the planar reciprocating vibrating screen, and it is easy to accumulate in the front of the screen, which leads to the decrease of screening efficiency. Based on the reverse engineering technology, using the wavy geometry formed during the earthworm (Pheretima guillelmi) moving as a bionic prototype, a bionic screen was designed to make the maize mixture migrate backward rapidly in the front of the screen. The contour curve of earthworm’s head in an axial contracted state was extracted and fitted to obtain its equation. Based on the difference of concave position of the lower surface’s wavy geometry during the earthworm moving, the motion of the bionic screen was divided into four postures, and the conversion between different postures of the bionic screen was realized by the cam drive mechanism. The kinematics simulation of the bionic screen was carried out through ADAMS, and the displacement and velocity of the bionic screen were analyzed. When the feeding mass of the maize mixture was set at 5 kg/s, 6 kg/s and 7 kg/s, the test results showed that the time of the maize mixture migrated (TOMMM) in the front of the bionic screen was shortened by 0.18 s, 0.71 s, and 1.36 s, respectively, compared with that of planar reciprocating vibrating screen. The total screening time (TST) of the bionic screen was shortened by 1.28 s, 1.33 s, and 1.53 s, respectively. The ability of the maize mixture to be migrated backward was improved. This study can provide a reference for the innovative design of the cleaning screen. Keywords: cleaning screen, maize grain harvester, material accumulation, earthworm, bionic design, motion characteristics DOI: 10.25165/j.ijabe.20211403.6534 Citation: Wang L J, Yu Y T, Zhang S, Feng X, Song L L. Bionic design and performance test of maize grain cleaning screen through earthworm motion characteristics. Int J Agric & Biol Eng, 2021; 14(3): 12–21.